Developing Discipline Character of Elementary School Students through Punishment - Rizka Qonita; Machful Indra Kurniawan; Mahardika Darmawan Kusuma Wardana (STAI Hubbulwathan Duri, 2022)
This study aims to implement the punishment method to develop the disciplined character of elementary student. The research used participatory action research with 35 third-grade elementary school students. The data was collected using observation consisting of several cycles. Each cycle consists of initial reflection, planning and observation, and reflection. Data analysis was carried out by converting the percentage of success indicators of discipline character. The results of this action research can be seen from the achievement of indicators of the success of the discipline character as follows (1) the discipline character of the realm of obeying the rules in the first cycle was 65% (less) and increased in the second cycle by 79% (good). (2) the discipline character of the realm of responsibility towards oneself in the first cycle by 67% (less), increasing in the second cycle by 73% (good), and (3) the disciplined character in the realm of implementing regulations in the first cycle by 63% (less) increasing in the first 2nd cycle of 71% (good). Thus, it can be concluded that the application of punishment to elementary school students can improve their disciplined character.